2006
DOI: 10.1086/506138
|View full text |Cite
|
Sign up to set email alerts
|

Eolian Erosion of Dusty Bodies in Protoplanetary Disks

Abstract: We discuss the possibility of the erosion of dusty bodies in protoplanetary disks by a subsonic laminar gas flow. Our analysis is based on wind tunnel experiments on centimeter-size dust targets in an air gas flow of 63 m s À1 at static gas pressures between 0.1 and 4.5 mbar. We compare the results to numerical calculations of gas flow through porous bodies and the resulting drag force on dust aggregates at the surface. Our studies imply that a dusty body can be efficiently eroded if the dynamic gas pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…There are other mechanisms which might also produce dust particles by destroying larger objects again, i.e. light induced erosion (Wurm & Krauss 2006b;Wurm et al 2008;Wurm 2007;de Beule et al 2013;Kocifaj et al 2011) or erosion by gas drag (Paraskov et al 2006). Therefore, as seen in observations as well as deduced from experiments there is no shortcoming of individual dust grainsmetal or silicate.…”
Section: Dust Supplymentioning
confidence: 95%
“…There are other mechanisms which might also produce dust particles by destroying larger objects again, i.e. light induced erosion (Wurm & Krauss 2006b;Wurm et al 2008;Wurm 2007;de Beule et al 2013;Kocifaj et al 2011) or erosion by gas drag (Paraskov et al 2006). Therefore, as seen in observations as well as deduced from experiments there is no shortcoming of individual dust grainsmetal or silicate.…”
Section: Dust Supplymentioning
confidence: 95%
“…In fact, the escape velocity is only on the order of 1 m s −1 . Paraskov et al (2006) put forward the idea that dusty objects might be destroyed in few orbits if cohesion does not dominate. They supported their idea by ground based wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Besides collisional fragmentation other destructive mechanisms are thinkable. These include gas drag (erosion by wind) as discussed by Paraskov et al (2006) or particle erosion by stellar insolation Kelling & Wurm 2009;de Beule et al 2013;Kocifaj et al 2010). It has also been suggested that the effect of aggregation is diminished by electrical charging and repulsion of aggregates (Okuzumi 2009).…”
Section: Introductionmentioning
confidence: 99%